(untitled) (Academicia Globe: Inderscience Research, 2024)
This article focuses on the linguistic and cultural analysis of ethnographism in the Kazakh language. Ethnographic vocabulary is formed and developed due to the generalization of observations of everyday facts of the language, the naming of life events and facts as a result of studying the environment and its various features and characteristics. It is described that all these are closely related to the people’s sense of identity, worldview, psychology, and language. Also, the main reason for the wide understanding of this word in many Turkic languages, firstly, in the ancient Turkic archaisms, secondly, in its homonymous division, and thirdly, in its syncretic nature, is expressed.